Structural investigations of phosphorus-nitrogen compounds.: 4.: Steric and electronic effects in dibenzylamino derivatives of hexachlorocyclotriphosphazatriene and 4,4,6,6-tetrachloro-2,2-diphenylcyclotriphosphazatriene - Besli, S; Coles, SJ; Davies, DB; Hursthouse, MB; Kiliç, A; Mayer, TA; Shaw, RA (Blackwell Munksgaard, 2002)
A systematic study is presented on the products of aminolysis of N3P3Cl6 (1) and N3P3Ph2Cl4 (4) with dibenzylamine. Two series of mono- and disubstituted derivatives of compounds (1) and (4), namely N3P3Cl5 [N(CH2Ph)(2)] (2) and N3P3Cl4 [N(CH2Ph)(2)](2) (3) and N3P3Ph2Cl3 [N(CH2Ph)(2)] (5) and N3P3Ph2Cl2 [N(CH2Ph)(2)](2) (6) [where (2), (3), (5) and (6) are new structures], are investigated in order to determine whether steric or electronic effects prevail in the formation of dibenzylamino-substituted cyclophosphazenes. The influence of an electron-releasing group (i.e. phenyl) on the stereochemistry and degree of substitution of the product is analysed by comparison of the above two series. The difference in unsymmetrically substituted endocyclic P-N bond lengths, Delta, is used as a measure of the degree of the electronic contribution, in combination with basicity constants, to quantify the degree of the electron-releasing capacity of the R group. In order to compare geminal versus non-geminal substitution, a difunctional secondary amine was used to form the compound N3P3Cl4 [NMe(CH2)(3) NMe] (7) (a reinvestigation) for inclusion in this study. It is shown that electron-releasing groups have a greater effect on the lengthening of P-Cl bonds as opposed to endocyclic P-N bonds and that this effect is greater in the non-geminal PRCl case than for geminal PCl2. However, steric effects are shown to be dominant in the reactions of dibenzylamine with N3P3 derivatives, with a disposition to a trans stereochemistry in bisdibenzylamino derivatives.
Keywords: Crystal; Products; Bond